Convergent landscape. 39 and a half as (multi) promotional intertext - Kopecka-Piech, Katarzyna (Journal of Education Culture and Society, 2020)
The purpose of this article is to provide a broader characterisation of the media convergence strategy applied by producers of the Polish commercial television station (TVN) series 39 and a half (39 i pół). In order to examine the convergence strategies of production, distribution, promotion and media usage, this paper analyzes metaphors of landscape, terrain, map and simulacrum. Moreover the concept of convergent (inter)text is proposed. In the case study of 39 and a half the author examines three main strategies implemented by the creators: the promotional virtualisation of reality, making virtual reality more real, and multiplied fiction. Transmedial and synergetic brands illustrate the hybridisation of the convergent and integrated media landscape.